2004
DOI: 10.1007/s00115-004-1752-1
|View full text |Cite
|
Sign up to set email alerts
|

Das so genannte spontane Liquorunterdrucksyndrom

Abstract: The new IHS classification describes under the paragraph 7.2.3 the headache attributed to spontaneous low CSF pressure. We report on four patients with such a headache and discuss the probable pathophysiology, including results published in the literature. It seems that not the low CSF pressure itself is the cause for the headache but the unphysiological, increased vasodilatation of intracranial and epidural veins. This dilatation of veins also shows up in the typical radiological findings with meningeal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Caffeine increases cerebral vasoconstriction by blocking adenosine receptors and leads to augmented CSF production by stimulating sodium-potassium pumps [59]. Mathew and Wilson [60] demonstrated a reduction in cerebral blood flow after the intravenous administration of caffeine benzoate for the treatment of PDPH.…”
Section: Treatmentmentioning
confidence: 99%
“…Caffeine increases cerebral vasoconstriction by blocking adenosine receptors and leads to augmented CSF production by stimulating sodium-potassium pumps [59]. Mathew and Wilson [60] demonstrated a reduction in cerebral blood flow after the intravenous administration of caffeine benzoate for the treatment of PDPH.…”
Section: Treatmentmentioning
confidence: 99%
“…By blocking adenosine receptors, caffeine increases cerebral arterial vasoconstriction, and leads to a decrease in cerebral blood inflow and brain blood volume. On the other hand, caffeine leads to augmentation of cerebrospinal fluid production by stimulating sodium-potassium pumps (35, 40). It seems that caffeine administration is a noninvasive and safe option that may prevent the use of invasive methods such as epidural blood patching, or epidural injection of NaCl 0.9% (35, 41).…”
Section: Resultsmentioning
confidence: 99%
“…These treatments seek to reduce cerebrospinal fluid loss through the dural holes and replenish it through increased fluid ingestion [12]. Although these tech niques are easy to apply and do not have any sig nificant negative side effects, there are insufficient data to recommend their usage in the prevention of PDPH [13,14]. The authors of a 2016 Cochrane review found insufficient proof that routine bed rest following a dural puncture prevents PDPH [12].…”
Section: Discussionmentioning
confidence: 99%